2020
DOI: 10.1177/1461444820966993
|View full text |Cite
|
Sign up to set email alerts
|

Returning to the digital world: Digital technology use and privacy management of women transitioning from incarceration

Abstract: Based on interviews with 75 women transitioning from incarceration, our research identifies technology access and skills barriers facing this population and their underlying concerns and motivations in navigating privacy online. Our results suggest precarious housing and financial situations, concerns about ex-partners, mental health issues, and lack of self-efficacy pose challenges for their access to and use of digital technologies and influence their online privacy perspectives. Many participants reported r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Seo et al [ 21 ] pointed out that a lack of self-efficacy poses challenges for incarcerated people in accessing and using digital technologies. Our results are consistent with this, and the results show that without adequate self-efficacy and internet self-efficacy, released people are at risk of digital exclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seo et al [ 21 ] pointed out that a lack of self-efficacy poses challenges for incarcerated people in accessing and using digital technologies. Our results are consistent with this, and the results show that without adequate self-efficacy and internet self-efficacy, released people are at risk of digital exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Gaps in digital competence can be related to not only actual skills, but also a person’s lack of confidence in his or her ability to use online services. Seo et al [ 21 ] showed that a lack of self-efficacy poses challenges for incarcerated people to access and use digital technologies. Consequently, this study focused on the significance of self-efficacy in the use of digital health care and social welfare services among incarcerated people in Finland.…”
Section: Introductionmentioning
confidence: 99%
“…With AI being embedded in many aspects of our lives, warnings are being raised about implications for furthering inequality or bias already existing in society [19,22,24]. A widely shared concern, for example, is that use of AI models will lead to legal, financial, or health initiatives disproportionately harmful to marginalized populations if these populations are not properly represented in training datasets [19,25,26]. In this paper, we argue that addressing this and other related issues requires rethinking beyond the legitimate critiques regarding representation and sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Gurusami (2019) found that the women lacked higher level digital skills that would allow them to escape the digital criminal record and surveillance from the carceral state, and that this made them susceptible to potential exploitation. Similarly, Seo et al (2020) highlight access barriers and a lack of higher level skills that would allow formerly incarcerated women to protect their privacy online, leading to “nothing to lose” attitudes that left the women vulnerable to various threats. In a similar vein, Ogbonnaya-Ogburu et al (2019) found that formerly incarcerated men were lacking employment- and job-search-specific digital skills, as they did not receive formal training and depended on family members for digital skills support.…”
Section: Literature Reviewmentioning
confidence: 99%